2008
DOI: 10.1021/jp8061493
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Phase Behavior and Charge Transport in Conjugated Polymer/Fullerene Blends

Abstract: The phase diagrams for three conjugated polymer/fullerene blends of interest for polymer solar cells, namely semicrystalline poly(3-hexylthiophene) (P3HT):methanofullerene [6,6]-phenyl C61-butyric acid methyl ester (PCBM), poly(2-methoxy-5-(3′,7′-dimethyloctyloxy)-p-phenylenevinylene) (MDMO-PPV):PCBM, and poly(2-methoxy-5-(2′-ethylhexyloxy)-p-phenylenevinylene) (MEH-PPV):PCBM, have been constructed based on X-ray scattering data and differential scanning calorimetery (DSC). Both melting point depression and gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
210
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(234 citation statements)
references
References 60 publications
22
210
1
1
Order By: Relevance
“…From these studies, we estimate that PCBM has a concentration greater than 40% wt in P3HT, which is consistent with previously reported estimates for bulk samples. [ 22 ] We believe that PCBM is dispersed as both molecular species within the disordered phase of P3HT (as shown below) and as aggregated PCBM domains. The observation of a fast interdiffusion coeffi cient indicates that the BHJ morphology formed after deposition will continue to change even under mild heating thus further complicating the characterization of its morphology.…”
Section: Interdiffusion Within P3ht/pcbm Bilayersmentioning
confidence: 89%
See 1 more Smart Citation
“…From these studies, we estimate that PCBM has a concentration greater than 40% wt in P3HT, which is consistent with previously reported estimates for bulk samples. [ 22 ] We believe that PCBM is dispersed as both molecular species within the disordered phase of P3HT (as shown below) and as aggregated PCBM domains. The observation of a fast interdiffusion coeffi cient indicates that the BHJ morphology formed after deposition will continue to change even under mild heating thus further complicating the characterization of its morphology.…”
Section: Interdiffusion Within P3ht/pcbm Bilayersmentioning
confidence: 89%
“…We are not aware of any reports of the percentage of crystallinity for thin fi lms of regioregular P3HT, but the results here suggest that the total crystallinity in the P3HT fi lm is low based upon simple consideration of the volume change during the mixing process. [ 22 ] As depicted in Figure 5 , the initial BHJ comprises a distribution of P3HT crystallites, PCBM aggregates, and a dispersion of PCBM (both molecular and small aggregates) in disordered P3HT. Upon annealing, our studies suggest that the size of the P3HT crystallites increases mainly within the fi rst 5 min of annealing regardless of the local concentration of PCBM (at approximately a 1:0.8 wt ratio) while the PCBM aggregates remain dispersed in the disordered regions of P3HT.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] However, phase behavior at molecular levels, including spatial arrangement of amorphous polymeric chain/fullerene in blends, has still been far from a complete understanding due to its complex nature. In 2008, two research groups reported the binary phase diagrams of semicrystalline poly(3-hexyl thiophene) (P3HT)/ PCBM blends 17 and amorphous poly(phenylene vinylene) (PPV) derivative/PCBM. 18 Recently, the molecular miscibility of polymer/fullerene blends and the extent of phase separation were investigated at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…This new finding recalls that poly(3-alkylthiophene)s were more organized when doped with iodine, 35 although the opposite behavior, i.e., destruction of ordering or decrease of crystallinity, has generally been expected when two materials are blended. 17,31 …”
Section: Introductionmentioning
confidence: 99%
“…Two different two-component nonequilibrium phase diagrams have been made 523 for P3HT:PCBM [121,122]. Figure 9 shows the expected phase behavior of P3HT: 524 PCBM in a melt or solidifying melt [121].…”
mentioning
confidence: 99%